Restorative Justice in the Resolution of Cases to Improve Legal Justice by the Malang Police Satreskrim PPA Unit (Advances in Police Science Research Journal, 2024)
Restorative justice has an important role in the National Police Chief's priority program for improve law enforcement performance. In today's era, laws in society are no longer based on the principles of positivism, but rather on progressive law, where law is the last resort in resolving criminal cases (ultimum remedium). This approach prioritizes completion problems peacefully or amicably and provide compensation to possible victims cannot be obtained through ordinary legal channels. However, restorative justice is still upheld Existing regulations such as the Republic of Indonesia State Police Regulation No. 8/2021. PPA Unit Malang Police are responsible for implementing restorative justice to assess its effectiveness. This research aims to evaluate the efficiency of restorative justice implemented by this unit, understand the processes involved in applying restorative justice to a case, and measure public perception of the issue. This research uses a case study method with interviews, observations, and document analysis as research instruments. Research result shows that the implementation of restorative justice in the Women and Child Protection Unit (PPA) has been running well and effectively.
Keywords: Restorative Justice, Satuan Reserse Kriminal, Unit PPA